2013
DOI: 10.1007/bf03341682
|View full text |Cite
|
Sign up to set email alerts
|

Taking Journal Clubs off Autopilot: A Case Study of Teaching Literature Evaluation Skills to Preclinical MD/PhD Students

Abstract: Researchers designed learner-directed journal clubs to develop literature evaluation skills in preclinical students. Sessions balanced student-led discussion with structured objectives and faculty support. During the pilot with preclinical MD/PhD students, self-rated mastery improved over all 17 measured objectives. Six exercises have since been incorporated into the full medical school curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…From the search of databases conducted (Figure 1), 457 papers were identified; on subsequent screening of the abstracts or full text of these articles, 15 met the minimum inclusion criteria described and were included in this review. 10,11,[17][18][19][20][21][22][23][24][25][26][27][28][29] Of the 15 studies included, 10 were conducted in the United States of America, two in the United Kingdom, and one each in Croatia, Ireland and the United Arab Emirates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the search of databases conducted (Figure 1), 457 papers were identified; on subsequent screening of the abstracts or full text of these articles, 15 met the minimum inclusion criteria described and were included in this review. 10,11,[17][18][19][20][21][22][23][24][25][26][27][28][29] Of the 15 studies included, 10 were conducted in the United States of America, two in the United Kingdom, and one each in Croatia, Ireland and the United Arab Emirates.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on how articles were selected for appraisal and discussion. Faculty or tutors selected articles for JCs in eight studies (Bahner; Chakraborti; Gokani; Quinn; Rosenthal; Willett; Williams; Lucia), 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 students selected the articles in three studies (Banerjee; Bertelsen; Curtis), 10 , 26 , 27 and in the remaining two studies (Berman, Currier), 17 , 28 the articles were selected via a collaboration between the students and the faculty or tutor. Sessions in many of the included studies were similar to a traditional journal club format.…”
Section: Resultsmentioning
confidence: 99%
“…This supported the findings of earlier research in which authors questioned the retention of EBP knowledge and skills after graduation from training programs and suggested that skills and knowledge might be lost if not updated by continuous training or engagement in local journal clubs. 8,[32][33][34] Plotting all data in a graph prior to class helped the course director identify resident performance outliers or discrepancies between the residents' QAS or SS and the group scores. Discrepancies indicated errors in identifying study design, randomization, or SS calculation errors.…”
Section: Discussionmentioning
confidence: 99%
“…(table 1) Reading and presenting journal articles help to use the information obtained for patient care or advancing knowledge in the field 20. Hence, it is important to critically analyse the findings presented in the article 21 22. Critical appraisal of a paper involves analysing the components of article in terms of its content, appropriateness of methodology used, reporting of results, reliability and validity of study, whether the conclusions drawn are appropriate and so on 23–26.…”
Section: Art Of Presenting An Articlementioning
confidence: 99%